POST-PANDEMIC ECONOMIC RESILIENCE AND STRUCTURAL CHANGES IN THE LABOUR MARKET: A HUMAN RESOURCE MANAGEMENT STUDY - Muhammad Syafri; Rahma Helal Al_ Jbour (Adisam Publisher, 2025)
The COVID-19 pandemic has had a significant impact on economic resilience and the global labour market, forcing structural changes affecting various sectors. This article analyses the dynamics of post-pandemic economic resilience as well as structural transformations in the labour market through a human resource management perspective. Research shows that digitalisation, automation and flexible working are becoming dominant trends in the labour market, shifting conventional skill requirements towards more technology and data-driven ones. In the context of economic recovery, companies need to develop responsive HR management strategies, such as reskilling, upskilling and supporting employee welfare. This approach aims to ensure operational sustainability and improve organisational competitiveness in the face of future challenges. This article concludes that the role of flexible and innovative HR is very influential in responding to post-pandemic change demands.